Non-destructive test examination of shielded metal arc welding of SS400 steel plate for pressure vessel application - Indra, Ida Bagus; Monanov, Murodih; Zaenudin, Mohamad; Saleh, Yasya Khalif Perdana (JTTM : Jurnal Terapan Teknik Mesin, 2025)
The global energy crisis caused by the limits of oil reserves urges the need for alternative energy solutions, including pyrolysis-based oil energy. In this study, we investigate the pyrolysis of corn cob biomass with varying particle sizes (3 mesh, 5 mesh, 7 mesh, and 10 mesh) to evaluate its effect on product yields and physical properties. Each experiment was conducted for 90 minutes using 300 grams of feedstock, which had been pre-dried in a microwave oven at 120°C for 2 hours. The results revealed that the bio-oil yield decreased with smaller particle sizes, from 31.52% at 3 mesh to 26.12% at 10 mesh. Conversely, bio-char yield increased from 37.48% to 46.47%, while bio-gas yield decreased from 31.00% to 27.42%. This suggests that excessively small particle sizes reduce bio-oil yield due to uncontrolled reactions despite their higher surface area. The bio-oil density ranged between 1.0235 and 1.0353 g/ml, indicating consistent physical properties across particle sizes. The inlet and outlet temperatures of the reactor (T1 and T2) and condenser (T3 and T4) remained relatively stable, indicating consistent condensation of pyrolysis gases into liquid bio-oil. This study has successfully provided insight into the optimization of a particle size of the waste processing of corn cob into energy by using the pyrolysis method